PENGARUH PENAMBAHAN Na2S2O5 DAN ASAM LAKTAT SERTA LAMA PENGADUKAN PARUTAN SINGKONG TERHADAP BAKING EXPANSION TEPUNG YANG DIHASILKAN - , THESA PASKARINA DAMAYANTI, Prof. Dr. Ir. Haryadi, M. App. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cassava (Manihot esculeta Crantz) is one of carbohydrate source that cheap and many cultivation in Indonesia. Cassava processing to flour is one way to make the application more easy. Cassava flour has lower of expansion so needs any modification. The modification in this research are mixing in lactic acid 3% (w/w) and oxidation using sodium metabisulphite or sodium bisulphite. The aim of this research is to know the effect of mixing duration in lactic acid 3% (w/w) that are 30, 45, 60, 75 and 90 minutes also the concentration of sodium metabisulphite (0,3